ChIP-seq reveals a role for CrzA in the Aspergillus fumigatus high-osmolarity glycerol response (HOG) signalling pathway - Castro, Patricia A. de; Chen, Chenxi; Couto de Almeida, Ricardo Sergio; Freitas, Fernanda Zanolli [UNESP]; Bertolini, Maria Celia [UNESP]; Morais, Enyara Rezende; Brown, Neil Andrew; Zambelli Ramalho, Leandra Naira; Hagiwara, Daisuke; Mitchell, Thomas K.; Goldman, Gustavo H. (Wiley-Blackwell, 2014)
Aspergillus fumigatus is an opportunistic pathogen and allergen of mammals. Calcium signalling is essential for A. fumigatus pathogenicity and is regulated by the CrzA transcription factor. We used ChIP-seq (Chromatin Immunoprecipitation DNA sequencing) to explore CrzA gene targets in A. fumigatus. In total, 165 potential binding peaks including 102 directly regulated genes were identified, resulting in the prediction of the A[GT][CG]CA[AC][AG] CrzA-binding motif. The 102 CrzA putatively regulated genes exhibited a diverse array of functions. The phkB (Afu3g12530) histidine kinase and the sskB (Afu1g10940) MAP kinase kinase kinase of the HOG (high-osmolarity glycerol response) pathway were regulated by CrzA. Several members of the two-component system (TCS) and the HOG pathway were more sensitive to calcium. CrzA